Physical mechanisms of photoinduced charge transfer in neutral and charged donor–acceptor systems. Issue 60 (29th November 2021) - Tian, Chunhua; Chen, Yichuan; Yan, Pen-ji; Sun, Mengtao; Quan, Jun
Abstract : In this paper, we provide visualization methods to reveal the physical mechanisms of photoinduced charge transfer in neutral and charged donor–acceptor systems. Abstract : In this paper, we provide visualization methods to reveal the physical mechanisms of photoinduced charge transfer in neutral and charged donor–acceptor systems. These visualization methods use the charge density difference and transition density matrix, which can promote deeper understanding of photoinduced charge transfer in donor–acceptor systems.